KAJIAN TINGKAT BAHAYA BANJIR DI DAS TIMBALUN KECAMATAN BUNGUS TELUK KABUNG - Muhammad Arif (STKIP Pesisir Selatan, 2016)
His research begins from phenomena of extended damage that result from flooding in DAS Timbalun. This research is purposed to analyze level of hazard and risk caused by flood and to formulate direction of policies for flood control in Bungus Teluk Kabung district, Padang. This research was descriptive and method using survey with sample area. Unit mapping was unit land that resulted from map overlay of land shape, slope, and land utilization. Unit land in research area was varied so that sample technique used here was stratified random sampling. Research findings show that: (1) level of flood hazard in research area is divided into two zones that are (a) medium level of flood hazard (5,383 Ha), (b) high level of flood hazard (1,170 Ha); (2) level of flood risk in research area is divided into three zones that are (a) low level of flood risk (5,229 Ha), (b) medium level of flood risk (219 Ha) and (c) high level of flood risk (1,035 Ha), (3) direction of flood control policies is prioritized in four alternative policies that are: (a) controlling flood rate of flow by establishing flood embankment to reduce flood risk, (b) improving overall drainage system to reduce level of flood risk, (c) arranging zones of flood level to establish early warning system, and (d) preventing housing development in zone of high level of flood hazard